FAKTOR PAJAK DAN FAKTOR LAIN TERHADAP TINGKAT HUTANG PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE TAHUN 2008-2010 - Anastasia Windarti, 09.05.52.0007; Poerwati, Tjahjaning (Students Journal of Accounting and Banking, 2012)
As a developing country, Indonesia shows a quite interesting phenomenon, which was the high rate of debt of many companies in Indonesia. This fact shows that the policy of leverage plays an important rule for the viability of the company. The main purpose of this research was to test empirically, any factors that influence the leverage for there are still inconsistence research results from the prior study.This study in addition to using this research tax factors that consisted of Corporate Tax Rate, and Non-Debt Tax Shield, influencing the leverage, and also predict other factors that influencing the leverage, which are Investment Opportunity Set (IOS), Profitability and Past Debt.Research object (samples) are about 90 manufacturing companies with period 2008 to 2010. Sample collection techniques is using porposive sampling. Data are tested by using multiple linear regression.The result of the study shows that the Investment Opportunity Set and Past Debt has significant positive effect on the Leverage. Corporate Tax Rate and Non-Debt Tax Shield had no significant positive effect on the Leverage, while Profitability had no significant negative effect on the Leverage.Keywords: Leverage, Corporate Tax Rate, Non-Debt Tax Shield, Investment Opportunity Set (IOS), Profitability, Past Debt.